Emotional Intelligence and Self-Control at Spread of Hoax News on Student Gadget Users - Wawan Agung Prastiyo; Ferdy Muzzamil; Arfian (Insight School Academy, 2023)
Gadgets are technological products that can present various news media, social networks, entertainment, etc. Gadget users with low self-control tend to be easily exposed to hoax news, while a hoax itself is information engineered to cover up accurate information. Self-control can be influenced by one's emotional intelligence to determine and adapt to managing all forms of communication. Research This aims to know if emotional intelligence influences self-control on the spread of hoax news gadget users at